Internationalisation processes in small and medium enterprises of the agrifood sector in Portugal - Noronha, Teresa de (2014)
During thel ast years we have observedin Portugal;as in the mosto f the European countriesa, n accentuated development concerning the internationalisation of the agri-food sector. As a result a better cornpetitive capacity is expected together with the technological reconversion of Portuguese enterprises, an improved organisational capacity of their managers as well as agressivity in the external markets. The internationalisation of enterprises, particularly of small and medium enterprises, may cause the development of their strategic capacity. The, agrifood sector is analyzed using four main topics: the recent evolution of the sector, the growth of the agiifood industry, the relative importanoe of the internationalisation process and the entrepreneurial and governemental strategies for internationalisation. The study allows to open the discussion on the importance that foreign capital has in the Portuguese SMEs atid in the exports value of the Portuguese agri-food sector, considering some subsectors in particular. We are able to conclude that therei s a growing interest of the agrifood European industriyn the Portuguese SMEs, speciallyi n those producing for the internal market. Further, conclusions coulbde arrived at regarding the growing capacitoy f a few large enterprisest o export parallelt o a decreasing participation of the "traditional" SMEs. They need to enter reconversion processesin order to improve specificities of the producatn d find niche markets.